Knowledge Management: An Alternative to Solve Educational Problems - Correa-Díaz, Ana María (2019)
This article aims to examine the way in which knowledge management helps to solve educational problems in the current global economy. The method employed was structured from an epistemological-documental analysis of successful educative models and the identification of relevant areas of change in high education institutions (HEI). As a result, it can be said that better codifications, curricula, and educational structures can be obtained thanks to knowledge management. In brief, through adequate knowledge management, faculties and departments at HEI have ample opportunities for development in interdisciplinary research projects. Besides, knowledge management helps to reduce costs, have new services for the students, and achieve teaching styles, as well as implement consultancies and personalized learning.